Hearts as large as the world: Charles Taylor's best account principle as a resource for comparative theologians - Hanson, Richard J. (The journal of religion & society, 2013)
This paper examines philosopher Charles M. Taylor's Best Account principle, an epistemic tool intended for use in multicultural societies, as one possible avenue for developing a more conceptually robust comparative theology. Specifically, I engage Taylor's Best Account, or "BA" principle, with some of the trajectories suggested by Francis X. Clooney's own interreligious encounters, and Clooney's theological reflections upon these experiences. I compare Clooney's interpretation of the dictum "to have a heart as large as the world" to Taylor's notion that the most adequate interpretation of human life is the one that makes the most sense in terms of the way human lives are actually lived (in essence, what Taylor means by "best account"), and use this as an opening to what I hope will be a wider conversation about the conceptual development of comparative theologies.